The land of stories : an author's odyssey/ 5 - Colfer, Chris, 1990- (Land of Stories ;, 2017)
"In order to end the Masked Man's literary army, the twins and their friends must enter Conner's short stories, where they find allies in unexpected places."--Provided by publisher.